Peran Politik dalam Pembentukan Kebijakan Bisnis Perdagangan Internasional - Yuniar Pangesti; Hendra Ibrahim (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
International trade is a means for exchanging international goods and services, and international trade policies are determined by both developed and developing countries. Political factors have a significant influence on international trade policy, both in terms of protecting domestic industry, encouraging exports, and privileges for developing countries. Global issues also play an important role in the formation of international trade policies by developed countries, such as free trade, sustainable development, and environmental protection. However, developed countries also face challenges in managing international trade relations, including balancing domestic economic and political interests and pressure from developing countries. Political factors also influence the direction and success of a country's international trade. Therefore, a good understanding of politics in international trade is very important in forming sustainable and profitable policies for a country.